2020
DOI: 10.1186/s13045-020-00985-0
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 released from GSDME-mediated pyroptotic epithelial cells participates in the tumorigenesis of colitis-associated colorectal cancer through the ERK1/2 pathway

Abstract: Background Pyroptosis is a form of proinflammatory gasdermin-mediated programmed cell death. Abnormal mucosal inflammation in the intestine is a critical risk factor for colitis-associated colorectal cancer (CAC). However, it is unknown whether pyroptosis participates in the development of CAC. Methods To investigate the role of gasdermin E (GSDME)-mediated pyroptosis in the development of CAC, Gsdme−/− mice and their wild-type (WT) littermate controls were challenged with azoxymethane (AOM) and dextran sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 35 publications
2
139
0
Order By: Relevance
“…These results are in agreement with previous reports demonstrated in cancer cells. 17,46 Moreover, it has been shown that TLR4 and RAGE receptors are implicated in HMGB1-induced vascular remodelling, 6,[47][48][49] and we found that TLR4 was the predominant receptor that mediated HMGB1-induced ERK1/2 and Drp1 activation. Taken together, our study suggests that ERK/Drp1 pathway plays an important role in HMGB1-induced PASMCs proliferation/ migration and pulmonary vascular remodelling.…”
Section: Discussionmentioning
confidence: 62%
“…These results are in agreement with previous reports demonstrated in cancer cells. 17,46 Moreover, it has been shown that TLR4 and RAGE receptors are implicated in HMGB1-induced vascular remodelling, 6,[47][48][49] and we found that TLR4 was the predominant receptor that mediated HMGB1-induced ERK1/2 and Drp1 activation. Taken together, our study suggests that ERK/Drp1 pathway plays an important role in HMGB1-induced PASMCs proliferation/ migration and pulmonary vascular remodelling.…”
Section: Discussionmentioning
confidence: 62%
“…The chronic inflammation caused by inflammatory mediators released from pyroptotic tissues increases the risk of tumorigenesis. HMGB1 released from pyroptotic epithelial cells promotes tumorigenesis of colitis-associated colorectal cancer by activating ERK 1/2 pathway (52). A recent study showed that pyroptosis triggered in the central hypoxic region of tumor provoked tumor progression and correlated with reduced survival (37).…”
Section: Application Of Pyroptosis In Tumor Treatmentmentioning
confidence: 99%
“…Our RNA-sequencing analysis revealed that genes related to pyroptosis were significantly upregulated in iEGFR lines (Figure 2C-D). Pyroptosis, a caspase-dependent form of proinflammatory programmed cell death, has emerging roles in the tumor microenvironment and has been recently implicated in promoting colitis-associated cancer 54,55 . Recent investigation of somatic evolution in IBD colonic epithelium revealed clonal expansions of mutations in the IL-17 pathway which render epithelium resistant to the IL-17A-induced pro-apoptotic response 56,57 .…”
Section: Discussionmentioning
confidence: 99%